1992
DOI: 10.1002/cne.903240403
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distribution and biological activity of pituitary adenylate cyclase‐activating polypeptide (PACAP) in the central nervous system of the frog Rana ridibunda

Abstract: The primary structure of frog pituitary adenylate cyclase-activating polypeptide (PACAP) has recently been determined and the results show that the sequence of PACAP has been highly conserved during evolution. In particular, the structure of the 1-27 fragment of PACAP is identical in frog and mammals. Using an antiserum raised against PACAP27, we have investigated the distribution of PACAP-containing neurons in the central nervous system of the frog Rana ridibunda by the immunofluorescence technique. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 37 publications
5
75
1
Order By: Relevance
“…The location of PACAP-containing neurons has also been investigated in the CNS of nonmammalian vertebrates including birds (Peeters et al, 1998;Nowak and Zawilska, 2003), amphibians (Yon et al, 1992(Yon et al, , 1993b) and fishes (Matsuda et al, 1997(Matsuda et al, , 2005bMontero et al, 1998;Jakab et al, 2004;Mathieu et al, 2004). Overall, the distribution of PACAP-immunoreactive cells exhibits a high degree of similarity with that of mammals.…”
Section: E Distribution Of Pituitary Adenylate Cyclaseactivating Polmentioning
confidence: 99%
See 2 more Smart Citations
“…The location of PACAP-containing neurons has also been investigated in the CNS of nonmammalian vertebrates including birds (Peeters et al, 1998;Nowak and Zawilska, 2003), amphibians (Yon et al, 1992(Yon et al, , 1993b) and fishes (Matsuda et al, 1997(Matsuda et al, , 2005bMontero et al, 1998;Jakab et al, 2004;Mathieu et al, 2004). Overall, the distribution of PACAP-immunoreactive cells exhibits a high degree of similarity with that of mammals.…”
Section: E Distribution Of Pituitary Adenylate Cyclaseactivating Polmentioning
confidence: 99%
“…Soon after the characterization of PACAP, the distribution of the peptide has been investigated in the brain of mammals Köves et al, 1991;Vigh et al, 1991;Kivipelto et al, 1992;Ghatei et al, 1993) and amphibians (Yon et al, 1992). In rat, radioimmunoassay measurements have revealed that the highest concentrations of PACAP occur in the hypothalamic area Ghatei et al, 1993).…”
Section: E Distribution Of Pituitary Adenylate Cyclaseactivating Polmentioning
confidence: 99%
See 1 more Smart Citation
“…All these hypothalamic nuclei contain neuroendocrine neurons that project to the median eminence and the neurointermediate lobe of the pituitary (Neary and Northcutt 1983;Tuinhof et al, 1994). In frog, some of these neurons express various hypophysiotropic neuropeptides such as corticotropin-releasing factor , thyrotropin-releasing hormone (Lamacz et al, 1989), somatostatin (Laquerrière et al, 1989), growth hormonereleasing hormone (Marivoët et al, 1988), gonadotropinreleasing hormone (Andersen et al, 1988;Collin et al, 1995), pituitary adenylate cyclase-activating polypeptide (Yon et al, 1992), ␣-melanocyte-stimulating hormone (Benyamina et al, 1986), melanin-concentrating hormone (Andersen et al, 1986), neuropeptide Y (Danger et al, 1985), enkephalins (Merchenthaler et al, 1989), calcitonin gene-related peptide (Mulatero and Fasolo, 1991), and galanin (Lázá r et al, 1991). That hcrt-immunoreactive fibers were not detected in the frog median eminence suggests that hcrts do not directly regulate the activity of adenohypophysial cells.…”
Section: Comparative Distribution Of Hcrt-related Peptides In the Cnsmentioning
confidence: 97%
“…It may be that the expression level of fGRP mRNA in the POA and MSA was too low to detect the signal in these brain regions with the present in situ hybridization or that some other undiscovered peptide(s) that cross-reacts with the antiserum against fGRP exists in the POA and MSA. Notwithstanding such discrepancy in the POA and MSA, many neuropeptides, such as thyrotropin-releasing hormone, galanin, PACAP, and somatostatin are known to be expressed in the SCN of the frog (Lamacz et al 1989, Laquerrière et al 1989, Lázár et al 1991, Yon et al 1992. We need to elucidate the co-localization of fGRP/fGRPRPs and these neuropeptides and their interaction in the frog SCN.…”
mentioning
confidence: 99%